Approach to a large rare diaphragmatic hernia in a patient undergoing cardiac surgery. Issue 2 (12th February 2019) - Brookes, John D L; Munasinghe, Charlene P; Croagh, Daniel; Goldstein, Jacob G
Abstract: Hernia of Morgagni is an unusual congenital defect of the sternal portion of the diaphragm. Its concurrence with cardiac surgical pathology is rarely described in the literature. Notwithstanding, huge hernia of Morgagni have been noted to cause serious peri-operative impediment and complications. We report the case of a 50-year-old gentleman with a massive Morgagni hernia that threatened strangulation during cardiopulmonary bypass. We describe the combined surgical approach undertaken to repair this hernia, with an accompanying review of the literature relating to misadventure and management of similar large hernia coinciding with cardiac surgery.